The Auditor-Firm Conflict of Interests: Its Implications for Independence: A Reply. - Goldman, Arieh; Barlev, Benzion (The Accounting Review, 1975)
This article presents response of the author on comments made by scholar Stephen E. Leob on the paper "The Auditor-Firm Conflict of Interests: Its Implications for Independence" that was published in the October 1974 of the periodical "The Accounting Review." In his comment on the article, Leob has raised two issues. The first concerns the behavior model of independence. He argues that this model is lacking because it concentrates only on the economic power aspect while it does not give recognition to all the variables that may affect an auditor in such circumstances. Second, he makes a specific suggestion for improving the model. He introduces the three factors used by scholar Jerome Carlin to explain the behavior of deviant attorneys and suggests that by using the Carlin model one can perhaps obtain a more realistic view of the auditor's reaction to client's pressure and economic power. The authors argue that Loeb's criticism of their model is unjustified. It results from a failure to realize that in an earlier article they were not concerned at all with predicting the behavior of individual auditors when subjected to client's pressures. In that article, the authors dealt with a different problem, namely, explaining why the independence issue has become so prevalent in the auditing profession.